Curcumin and Curcumol Inhibit NF-κB and TGF-β1/Smads Signaling Pathways in CSE-Treated RAW246.7 Cells. (17th March 2019) - Li, Ning; Liu, Tian-Hao; Yu, Jing-Ze; Li, Chen-Xi; Liu, Yang; Wu, Yue-Ying; Yang, Zhong-Shan; Yuan, Jia-Li
Abstract : E-Zhu ( Curcuma zedoaria ) is known as a classical traditional Chinese medicine and widely used in the treatment of cancers, cardiovascular disease, inflammation, and other diseases. Its main components include curcumol and curcumin, which have anti-inflammatory and antifibrosis effects. Here we established an in vitro inflammatory injury model by stimulating RAW246.7 cells with cigarette smoke extract (CSE) and detected the intervention effects of curcumin and curcumol on CSE-treated Raw246.7 macrophage cells to explore whether the two compounds inhibited the expression of inflammatory cytokines by inhibiting the NF- κ B signaling pathway. We detected the antifibrosis effects of curcumin and curcumol via TGF- β 1 /Smads signaling pathways. The model of macrophage damage group was established by CSE stimulation. Curcumol and curcumin were administered to Raw246.7 macrophage cells. The efficacy of curcumol and curcumin was evaluated by comparing the activation of proinflammatory factors, profibrotic factors, and NF- κ B and TGF- β 1 /Smads signaling pathway. In addition, CSE-treated group was employed to detect whether the efficacy of curcumol and curcumin was dependent on the NF- κ B signaling via the pretreatment with the inhibitor of NF- κ B. Our findings demonstrated that curcumol and curcumin could reduce the release of intracellular ROS from macrophages, inhibit the NF- κ B signaling pathway, and downregulate the release of proinflammatory factor. Curcumol and curcumin inhibited the TGF- β 1 /Smads signaling pathway and downregulated the release of fibrotic factors. Curcumin showed no anti-inflammatory effect in CSE-treated cells after the inhibition of NF- κ B. Curcumol and curcumin showed an anti-inflammatory effect by inhibiting the NF- κ B signaling pathway.